2009
DOI: 10.1007/s00467-009-1299-2
|View full text |Cite
|
Sign up to set email alerts
|

Dent’s disease manifesting as focal glomerulosclerosis: Is it the tip of the iceberg?

Abstract: Dent's disease is an X-linked proximal tubulopathy. It often manifests in childhood with symptoms of Fanconi syndrome and low-molecular-weight proteinuria. We describe four boys from three unrelated families whose only presenting symptoms of Dent's disease were nephrotic-range proteinuria and histological findings of focal segmental and/or global glomerulosclerosis. In all families, a causal mutation in the CLCN5 gene, encoding a voltage-gated chloride transporter and chloride-proton exchanger, was identified.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
80
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(85 citation statements)
references
References 13 publications
2
80
0
Order By: Relevance
“…There are several possible explanations for this delay in diagnosis. First, the histological findings of kidney biopsies in patients with Dent disease are nonspecific, ranging from normal to FSGS-like lesions [10,11]. Murakami and Kawakami [7] reported that the kidney biopsies of patients with J-Dent revealed various abnormal glomerular findings in 34 % (11/32 cases).…”
Section: Discussionmentioning
confidence: 99%
“…There are several possible explanations for this delay in diagnosis. First, the histological findings of kidney biopsies in patients with Dent disease are nonspecific, ranging from normal to FSGS-like lesions [10,11]. Murakami and Kawakami [7] reported that the kidney biopsies of patients with J-Dent revealed various abnormal glomerular findings in 34 % (11/32 cases).…”
Section: Discussionmentioning
confidence: 99%
“…The level of proteinuria often reaches the nephrotic range (13,14). This hampers the diagnosis of Dent disease and explains why it is often treated as NS (15)(16)(17). The current results indicated that urinary α1-microglobin increased markedly (200-300-fold above the upper limit of normal, 0-12 mg/L) in all 10 patients with Dent disease, and the ratio of urinary α1-microglobulin to microalbumin was greater than 1.…”
Section: Resultsmentioning
confidence: 54%
“…Excepting very few cases, the OCRL mutations associated with Dent disease 2 do not overlap with those causing Lowe syndrome. 10,20,24 Missense mutations occur in the middle region of the gene (exons 9-15), whereas truncating mutations are found exclusively in the first 7 exons; the OCRL mutations associated with Lowe syndrome are located instead in the 3 0 region of the gene (exons [9][10][11][12][13][14][15][16][17][18][19][20][21][22] and involve all three functional OCRL1 domains, whereas frameshift and nonsense mutations cluster in exons [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. The different distribution of OCRL mutations in Dent disease 2 and Lowe syndrome suggests a genotype-phenotype correlation that has yet to be thoroughly explored.…”
Section: Resultsmentioning
confidence: 99%
“…Different groups of researchers have recently reported on case series of patients with atypical or rare Dent disease 1 phenotypic signs, such as episodic night blindness, 14 Bartter-like syndrome, 15,16 growth hormone deficiency, 17 and proteinuria with histological evidence of focal segmental glomerulosclerosis. 18,19 Dent's disease patients carrying OCRL gene mutations (Dent disease 2, MIM#300555) have none of the classic symptoms accompanying renal tubulopathy in Lowe syndrome, that is mental retardation, bone disease, growth retardation, congenital cataracts, delayed motor milestones. This milder phenotype is not attributable to less severe changes in protein expression or enzyme activity, as both are significantly reduced or absent.…”
Section: Introductionmentioning
confidence: 99%